Can ICT-enabled real-time data contribute to adaptive management in development programming?. Issue 3 (3rd April 2019) - Barnett, Inka; Hernandez, Kevin; Ramalingam, Ben; Levy, Anna; Oppenheimer, Carrie; Valters, Craig
ABSTRACT: This article aims to explore whether ICT-enabled real-time data (RTD) systems can help to improve the operationalisation of adaptive management of international development programmes. Using a qualitative multi-method approach consisting of 48 semi-structured key expert interviews and four exploratory case studies, we found that RTD can successfully inform rapid tactical adaptive management in development programmes but is, on its own, of only limited use for most strategic adaptive management. The research identified multiple contextual barriers to the use of RTD for adaptive management. These barriers need to be addressed to realise the full potential of real-time adaptive management of programmes.